Festival as a Learning Space: Local Wisdom-Based Arts and Culture Education Through the Watu Pecah Mountain Foot Festival to Strengthen Student Character - Enys Kartika; Anik Juwariyah; Retnayu Prasetyanti; Warih Handayaningrum; Indar Sabri (Universitas Pendidikan Mandalika, 2026)
This study aims to describe the implementation of arts and culture education based on local wisdom through the Watu Pecah Mountain Foot Festival and to examine its contribution to the development of students’ character at SMPN 1 Ambulu, Jember. This research employed a descriptive qualitative approach with data collection techniques consisting of participatory observation, in-depth interviews, and documentation. Informants were selected using a purposive sampling technique, involving students, arts and culture teachers, and the caregivers of Sanggar Seni Kartika Budaya Jember. Data were analyzed using an interactive model comprising data reduction, data display, and conclusion drawing, with validity ensured through source and method triangulation. The results revealed that the learning process was implemented through five ethnopedagogical stages: orientation, exploration of local wisdom, meaning construction, contextual activities, and reflection and evaluation. Through active participation in festival activities, students developed various character values, including mutual cooperation, solidarity, responsibility, discipline, social awareness, and tolerance. Compared with conventional learning approaches, the festival provided a more authentic, contextual, and meaningful learning experience because it engaged students physically, cognitively, and emotionally. This study confirms that local wisdom embedded in authentic cultural practices can serve as an effective learning resource for character education at the secondary school level.